2014
DOI: 10.1261/rna.044602.114
|View full text |Cite
|
Sign up to set email alerts
|

A homolog of lariat-debranching enzyme modulates turnover of branched RNA

Abstract: Turnover of the branched RNA intermediates and products of pre-mRNA splicing is mediated by the lariat-debranching enzyme Dbr1. We characterized a homolog of Dbr1 from Saccharomyces cerevisiae, Drn1/Ygr093w, that has a pseudometallophosphodiesterase domain with primary sequence homology to Dbr1 but lacks essential active site residues found in Dbr1. Whereas loss of Dbr1 results in lariat-introns failing broadly to turnover, loss of Drn1 causes low levels of lariat-intron accumulation. Conserved residues in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 48 publications
7
37
0
Order By: Relevance
“…S1). This K m value agrees with a previous report of a K d of 0.5 μM for bRNA binding to yDbr1 (31). Electrophoretic analysis of the substrate before and after exposure to Dbr1 indicated that the substrate was completely debranched by Dbr1 (Fig.…”
Section: Resultssupporting
confidence: 92%
“…S1). This K m value agrees with a previous report of a K d of 0.5 μM for bRNA binding to yDbr1 (31). Electrophoretic analysis of the substrate before and after exposure to Dbr1 indicated that the substrate was completely debranched by Dbr1 (Fig.…”
Section: Resultssupporting
confidence: 92%
“…Notably, a positively charged surface of the N-domain of Cwf19L2 clamps over the lariat junction( Fig. 4c), suggesting a role in modulating the turnover of branched intron 28 ; whereas the bridging helix and the C-domain together bind the BPS/U2 duplex and the 3'-tail of the intron (Fig. 4c); this organization is consistent with the observation that Cwf19L2 may help displace and unwind the BPS/U2 duplex during spliceosome disassembly 49 .…”
Section: The Transition From the P To Ils1 Complexsupporting
confidence: 80%
“…The distinct orientation of the RNaseH-like domain is likely facilitated by its close interactions with Cwf19L2 in human (Cwf19 in S. pombe). Our structural analysis and published studies support the conclusion that Cwf19L2 may have multiple roles during splicing28 . The precise functional annotation of Cwf19L2 requires further biochemical investigation.…”
supporting
confidence: 86%
“…However, the covalent nature of the branch would present a persistent barrier to the exonuclease activities of the exosome, resulting in a futile cycle of oligo(A) addition and degradation, potentially explaining why the dominant oligo(A) tails at the 3 ′ termini of lariat introns at steady state extended only one nucleotide, as compared with other exosome substrates for which oligo(A) tails are longer and recruitment of the exosome to the oligo(A) tail would generally lead to processive degradation of the RNA (Jia et al 2011;Wlotzka et al 2011). Nevertheless, the exosome embodies not only exonucleolytic activities but also an endonucleolytic activity (Lebreton et al 2008), which could potentially bypass the branched structure and account for the endonucleolytic cleavage of lariats stabilized in a dbr1Δ strain, cleavage that has been observed previously (Ooi et al 1998;Garrey et al 2014) and likely accounts for the population of 3 ′ reads that mapped to the intron body, upstream of the branch (Fig. 3D).…”
Section: Insight Into Lariat Intron Processingmentioning
confidence: 83%